The creation of a quadcopter remote controlling cross-platform software application (Transport systems and technologies, 2019)
A quadcopter – is an unmanned flying machine on the remote control. They consist of 4 arcs on which the motor and propeller are mounted. If you install four propeller motors on a light carbon fiber case, fiberglass or light wood and connect them to the remote control via a control board equipped with gyro stabilization, you can get a simple drone with components that have almost endless designs.A quadcopter remote controlling software on the base of microcontrollers Arduino and ESP is created. The developed software product is a cross-platform application for quadcopter control, and the software developed for used microcontrollers can be easily modified and supplemented with new functions. In the development process, modern technologies were used, such as C #, XAML, Wi-Fi, UWP who proved they are reliable enough to use. The result of this work is the simplified creation of quadrocopter, including the use of cheaper components and the expansion of the quadrocopter functionality.
Keywords: quadcopter, Arduino, ESP, C#, UWP, cross-platform, microcontroller boards, Wi-Fi.